2010
DOI: 10.1177/0957154x09338336
|View full text |Cite
|
Sign up to set email alerts
|

J.-M. G. Itard’s 1825 study: movement and the science of the human mind

Abstract: Jean-Marc Gaspard Itard's 1825'Study of several involuntary functions of the apparatus of movement,gripping, and voice' discusses 10 individuals with uncontrolled movements but no other significant impairments.Thus, otherwise normal people move in inappropriate ways against their better judgement. Although the study contains the first clinical description of Tourette Syndrome, it has received little attention beyond that notice. Examined in its entirety and in its cultural context, Itard's study characterizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Tik bozukluklari ilk kez 19. yüzyilda, Fransiz nörolog Jean Marc Itard'in Marquise de Dampierre olgusu ile 1825 yilinda yazina geçmi §tir (8). Fransiz asilzadesi Dampierre Markizi, 7 yaçinda baçlayan hareket tiklerinin ardindan, çiglik ve garip bagirmalari içeren istemsiz sesler çikarmasiyla birlikte sosyal yönden kabul edilemez türden vokalizasyonu ve eklenen koprolali nedeniyle 85 yaçina kadar tecrit edilmiçtir.…”
Section: Tarihçeunclassified
“…Tik bozukluklari ilk kez 19. yüzyilda, Fransiz nörolog Jean Marc Itard'in Marquise de Dampierre olgusu ile 1825 yilinda yazina geçmi §tir (8). Fransiz asilzadesi Dampierre Markizi, 7 yaçinda baçlayan hareket tiklerinin ardindan, çiglik ve garip bagirmalari içeren istemsiz sesler çikarmasiyla birlikte sosyal yönden kabul edilemez türden vokalizasyonu ve eklenen koprolali nedeniyle 85 yaçina kadar tecrit edilmiçtir.…”
Section: Tarihçeunclassified
“…Tourette Sendromu (TS) çocukluk veya ergenlik çağında başlayan, binde 4-6 sıklıkla görülen en az bir yıl süren motor ve vokal tiklerle karakterize nöropsikiyatrik bir hastalıktır (1,2,3). Çocukluk veya ergenlik çağında başlangıç, yaygınlaşmış tik ve istemsizce söylenen argo sözler olmak üzere 3 bileşeni vardır (3).Tourette Sendromunun da içinde bulunduğu tik bozuklukları ilk kez 1825'te Fransız bir hekim olan Jean Marc Itard tarafından 'Dampierre Markizi' olgusu ile bildirilmiştir (4). Markizi'nin semptomları 7 yaşında başlamıştı ve evlendikten sonra dahi alevlenerek devam etmişti.…”
Section: Introductionunclassified
“…Normalde kibar bir insan olmasına rağmen toplum tarafından kabul edilemeyen tikleri ve küfürlü konuşması nedeni ile hayatının büyük bir kısmını sosyal hayattan uzak geçirmişti. 90 yaşını aştıktan sonra, ölmeden önce dahi küfürlü konuşması devam ediyordu (3)(4)(5). 1884'te Gilles de la Tourette'nin, Charcot'un araştırma ekibine katılması sonrası birlikte, içinde Markizi'nin de olduğu bir takım hareket bozukluğu olan hastalar ile sınıflandırma çalışmaları yaptıkları sırada, Gilles de la Tourette maladie des tics cotnpulsifs (kompulsif tikler hastalığı) adını verdiği klinik durumu izole etti (3)(4)(5).…”
Section: Introductionunclassified
“…Tourette Syndrome (TS) is a complex hyperkinetic neurodevelopmental disorder, which is characterized by involuntary motor and/or vocal tics. The first clinical description of this syndrome occurred in 1825 by Jean-Marc Gapard Itard, the Chief Physician at the National Institute for Deaf-Mutes in Paris, who studied 10 individuals with TS symptomology (Newman, 2006;Newman, 2010). Itard described individuals with TS as follows: "When the muscles which animate our lives are no longer controlled by the will, because of morbid stimulus provokes contractions and produces convulsions, these violent and repetitive movements are especially disorganized, tumultuous, and nonfunctional" (Newman, 2006, p. 339).…”
Section: Clinical Discovery Of Tourette Syndromementioning
confidence: 99%
“…Comorbidity, with then unknown disorders, was also described such as Obsessive-Compulsive Disorders (OCD), Attention Deficit Hyperactivity Disorder (ADHD), selfinjurious behaviors, and emotional distress (Newman, 2006). Despite having the first clinical description of TS, Newman (2010) indicated that at the end of Itard's study, the goal was not to name the syndrome that ailed his patients, but rather to examine the symptoms, origins, and treatment.…”
Section: Clinical Discovery Of Tourette Syndromementioning
confidence: 99%